The Perception of Perhumas Central Java Members on Principles of PR Performance in Islam - Trimanah, Trimanah; Wulandari, Diah (Jurnal The Messenger, 2018)
Public Relations as a matter of study and implementation of theory, can not be separated from the influence of religious scriptures embraced by individuals. For a Moslem, the Qur'an and Hadith are the guides and sources of knowledge that are used as a reference by Public Relations Officer in the work. Arthur W. Page proposes work principle that must be owned by Public Relations: Tell the Truth, Prove It with Action, Listen to the Customer, Manage for Tomorrow, Conduct Public Relations as If The Whole Company Depends on It, Remain Calm, Patient and Good Humor. This research discusses about the Perception of Perhumas Central Java Members in viewing the principles of public relations performance in Islamic Shari'a view. The method used in this research is descriptive qualitative, using 4 informants. Analytical techniques used are interactive analysis model, data collection was done by structured interviews and literature study.